Moxibustion combined with Traditional Chinese Medicine ointment massage for a patient with grade II myelosuppression after chemotherapy for pancreatic cancer (艾灸联合中药膏摩疗法治疗1例胰腺癌化疗后II度骨髓抑制患者的护理) - SU Zhichao (苏志超); LIU Shuhong (刘书红) (Association of Integrative Nursing, 2023)
This paper investigated the effect of moxibustion combined with Traditional Chinese Medicine ointment massage for a patient with grade II myelosuppression after chemotherapy for pancreatic cancer, and summarized related nursing measures. The compressive nursing assessment and determination of severity of myelosuppression were conducted before treatment. Based on the Traditional Chinese Medicine syndrome differentiation, moxibustion combined with Traditional Chinese Medicine ointment massage was carried out to relive the symptoms of myelosuppression caused by chemotherapy for pancreatic cancer (本文总结1例艾灸联合中药膏摩疗法治疗胰腺癌化疗后骨髓抑制的护理经验。全面评估患者情况, 明确骨髓抑制分度, 基于中医辨证, 采用艾灸联合中药膏摩肿瘤绿色调护, 补益脾胃、化痰散瘀, 有效减轻患者骨髓抑制程度, 对提高患者生活质量具有积极意义。)